2014
DOI: 10.1177/1062860614536767
|View full text |Cite
|
Sign up to set email alerts
|

Technology Integration Performance Assessment Using Lean Principles in Health Care

Abstract: This study assesses the impact of an automated infusion system (AIS) integration at a positron emission tomography (PET) center based on "lean thinking" principles. The authors propose a systematic measurement system that evaluates improvement in terms of the "8 wastes." This adaptation to the health care context consisted of performance measurement before and after integration of AIS in terms of time, utilization of resources, amount of materials wasted/saved, system variability, distances traveled, and worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…After the application of these tools, interventions were carried out by the authors, obtaining in several cases a reduction in the workload, length of stay, treatment, waiting and, consequently, a reduction in lead time. In contrast, a study found that after implementing changes, there was an increase in costs [47].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…After the application of these tools, interventions were carried out by the authors, obtaining in several cases a reduction in the workload, length of stay, treatment, waiting and, consequently, a reduction in lead time. In contrast, a study found that after implementing changes, there was an increase in costs [47].…”
Section: Discussionmentioning
confidence: 91%
“…Among these interventions, we can highlight reorganization of the physical structure [19,30,39,41,45], review of work processes [38,[46][47][48][49], development and standardization of documents [29,[50][51][52][53] and team training [24,25,41,54,55], among others. A single article that aimed to evaluate the current process of a service did not present any type of intervention [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…D'Andreamatteo et al (2015 and Holden et al (2015) demand the investigation of national differences, while Andersen and Røvik (2015) ask for adaption of Lean Philosophy to the local context. A related topic is the investigation of Lean Healthcare's influence on healthcare employees and their engagement in Lean Implementations (Abdelhadi 2015;Holden et al 2015;Rico et al 2015).…”
Section: Future Research Tendenciesmentioning
confidence: 99%